Pengaruh Terpaan Iklan Nacific di Instagram terhadap Keputusan Pembelian Produk Nacific pada Followers Akun @nacificofficial.id - Didiek Tranggono; Ajeng Nidita Putri; Juwito Juwito (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2020)
This research discusses the effect of exposure to nacific advertisements on instragram on purchasing decicions for nacific prodctson followers of he @nacificofficial.id. This research uses quantitative approach and the analytical method used is multiple linear regression. The object of this research is Jang Hansol version of Nacific ad which about answers question about ‘Fresh Herb Origin’ product. Meanwhile, the subject is followers Nacific’s official account on Instagram, @nacificofficial.id who have watched the ad. Primery data collection using a questionnaire to 100 respondents. The results showed that exposure of Nacific ad on Instagram has positive influence on purchase decision of the advertised product. Thus, H1, H2 and H3 are accepted, that means frequency, duration and intensity have influence on purchase decision which have indicators: product choices, brand choices, supplier choices, time of purchase, purchase quantity and payment method